An investigation of the factors influencing the sustainability of small- and medium-scale electrical contracting enterprises (SMECEs) in the Cape Peninsula - Visser, Charl (Department of Mechanical Engineering, 2014)
This study focuses on small- to medium-scale electrical enterprises (SMECEs) in the Cape Peninsula, and specifically on electrical contractors with fewer than 25 employees. The objectives of this study are threefold: Firstly, the study reviews the position of current SMECEs, their economic contribution to the economy, their origin and establishment, the lifespan of the business, as well as the level of education of the individuals involved in the business. Secondly, it determines the constraints and limitations that may lead to the failure of these businesses. And, thirdly, it identifies the factors that may enable SMECEs to become sustainable or successful enterprises. A two-phased research method was used to collect information from owners of electrical contracting firms. This method involved the use of a pilot survey questionnaire and a main survey questionnaire. The pilot and main questionnaires were used to obtain data pertaining to the electrical contracting industry and owners of such firms. More specifically, this data includes information on the background of the company and its owner, the establishment of the business and its employment structure, as well as its work history, current operations and future objectives. It also looked at the constraints and limitations faced by these SMECEs, and identified specific factors that may enhance their sustainability. These questionnaires revealed that the constraining factors could be placed into two main categories, viz. management and labour. Management problems, for instance, included poor cash flow because of slow payment by clients, a lack of management skills on the part of business owners, and an inability to calculate project costs accurately. Labour problems, on the other hand, included an unreliable work force with no proper or effective work ethic, a lack of skilled and trained labour, and a work force that was inadequately skilled as either electricians or assistants. Among the factors that are necessary to ensure the success and sustainability of SMECEs, were the following: Business owners need to deal personally with problems and constraints and must learn how to avoid them. They must improve their management and planning ability, and must be able to understand the market. Their business must offer good workmanship and quality of service, and they must be able to complete their projects successfully. A reliable skilled work force is imperative, as are marketing skills and the ability to ensure the controlled growth of the firm. The following recommendations are made to owners of SMECEs: In order for their business to be successful and sustainable, they need to identify training courses that can assist their current contracted labour force. Business owners themselves also need to attend tendering and cost-control courses to improve the running and management of their business. They need to support the education and training of their work force and to employ skilled workers. Furthermore, they must ensure that the scope of the electrical contract is explained to the work force and that there is a written contract from the client, setting out the conditions of payment, in order to prevent late payment and thus cash flow problems.